MAKNA IDENTITAS BUDAYA DAN KONFLIK ANTARETNIS DALAM NARASI HOLLYWOOD: ANALISIS FILM “CRAZY RICH ASIANS” PERSPEKTIF SEMIOTIKA NARATIF GREIMAS - Muhammad Abdurrahman Arsi; Alex Sobur (MediaTor (Jurnal Komunikasi), 2019)
This thesis entitled ‘the meaning of Cultural Identity and inter-ethnic conflict in Crazy Rich Asians the movie’ aims to find out the meaning of Asian-American cultural identity and conflict behind its narrative. This qualitative research applied Greimas’s narrative semiotics analysis and borrows few of Christian Metz’s film semiotics. Greimas narrative semiotics is a theory and method that can be used to investigate signs in the narrative text whether expressed in the surface structure of storytelling, or implied in the inner structure of the text. Results of this study found that the meaning of Asian-American cultural identity and conflict illustrated through the surface structure of storytelling which is represented through six actants, namely sender, receiver, subject, object, and traitor. Through the traitor actant, the power that prevents subject from reaching his object are prejudice, social status, and personal revenge, while the strength that supports subject in facing these obstacles are love and courage. Through functional schemes, conflict dynamics illustrated through the sequence of events. After analyzing the inner structure with semiotic square, it is known that the main theme underlying the outer structure of storytelling is the dichotomy between West vs East and courage vs fear, along with subterms that negate and imply the two main terms